A novel intestinal-restricted FXR agonist. Issue 15 (1st August 2017) - Wang, Hong; Zhao, Zhou; Zhou, Jiyu; Guo, Yitong; Wang, Guangji; Hao, Haiping; Xu, Xiaowei
Graphical abstract: Highlights: A new FXR agonist Fex-3 was developed. Fex-3 could selectively activate intestinal FXR and promote the expression of BSEP and SHP while suppressing CYP7A1. We demonstrated that Fex-3 targeted on FXR in ileum and has better selectivity than Fex. Abstract: In this study, a new intestinal-restricted FXR agonist named fexaramine-3 (Fex-3) was developed and investigated both in vitro and in vivo . Fex-3 could selectively activate intestinal FXR and promote the expression of BSEP and SHP while suppressing CYP7A1 which is involved in bile acids syntheses better than the reported intestinal-restricted FXR agonist fexaramine (Fex). We demonstrated that Fex-3 targeted on FXR in ileum and has better selectivity than Fex. And the study of utilizing Fex-3 to reduce obesity was undergoing.